Techniques for displaying optically distorted sculpture (anamorphic sculpture) in contemporary art (Al-Academy, 2024)
The current research is concerned with studying the techniques for displaying distorted sculpture in contemporary art, as we addressed the topic of distorted art, and examined the techniques for showing it in three-dimensional formation. Within spatial boundaries that we limited to the continents of Europe and America) and temporal boundaries (1990 - 2020 AD). The research was structured in four chapters. The first chapter included the methodological framework of the research and several titles that represent the general picture of scientific research. As for the second chapter, the theoretical framework of the research, it included three sections. In the first section we dealt with the concept of anamor physique, while the second section was devoted to studying the art of distorting the perspective of authorities and institutions. As for the third section, we presented a brief study of display techniques in contemporary sculpture. Then we concluded the chapter with indicators of the theoretical framework. The third chapter devoted the research procedures to looking at the research community, and explaining all its realistic details, and what are the most important sources for finding the original community, as well as identifying the sample, as there were four deformed sculptural works as models for the sample, and we relied on observation as a tool. For research, the chapter then included an analytical study of selected or intentionally selected models. The fourth chapter included a set of research results and conclusions, including: - Contemporary sculptors relied on algorithms and mathematical equations as one of the techniques that enabled them to create distorted subterranean formations. Then we concluded the research with a set of service proposals and recommendations for institutions related to the research topic